2022
DOI: 10.3390/ijms23031244
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Biomaterials in Peripheral Nerve and Spinal Cord Injury: A Review

Abstract: Peripheral nerve and spinal cord injuries are potentially devastating traumatic conditions with major consequences for patients’ lives. Severe cases of these conditions are currently incurable. In both the peripheral nerves and the spinal cord, disruption and degeneration of axons is the main cause of neurological deficits. Biomaterials offer experimental solutions to improve these conditions. They can be engineered as scaffolds that mimic the nerve tissue extracellular matrix and, upon implantation, encourage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 145 publications
0
30
0
Order By: Relevance
“…These medical devices can carry a large variety of therapeutic agents (e.g., drugs, neurotrophins, and antibodies) and release them locally at the injury site [ 68 ]. An overview of the conventional and non-conventional treatments is presented in Table 1 and Figure 1 .…”
Section: Drug Delivery To the Spinal Cord: The Role Of Biomaterials I...mentioning
confidence: 99%
“…These medical devices can carry a large variety of therapeutic agents (e.g., drugs, neurotrophins, and antibodies) and release them locally at the injury site [ 68 ]. An overview of the conventional and non-conventional treatments is presented in Table 1 and Figure 1 .…”
Section: Drug Delivery To the Spinal Cord: The Role Of Biomaterials I...mentioning
confidence: 99%
“…Numerous studies indicated that fiber-like or channel-like microstructures arranged longitudinally could guide neurite growth during neurite growth [ [27] , [28] , [29] , [30] ]. Recent studies have found that introducing axially aligned microchannel structures into the bio-scaffold could effectively guide and significantly facilitate neurite extension and Schwann cell migration [ 31 , 32 ]. As a common material for bone tissue engineering, polycaprolactone (PCL) has good biocompatibility, fewer acid decomposition products, good mechanical properties, and a slow degradation rate, providing time for tissue remodeling [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, increasing research interest has been noticed in designing advanced repair strategies for spinal cord regeneration. Particular attention has been drawn to biomaterials and nanotechnologyenabled products for the controlled delivery and sustained release of various moieties, including drugs, bioactive molecules, imaging agents, and cells [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%